KOMPETENSI PEDAGOGIK, PENTING? - Khaila Melani, Suci Yuniati, Annisah Kurniati, Depriwana Rahmi (YAYASAN CENDEKIA CITRA GEMILANG, 2024)
This research aims to determine the importance of pedagogical abilities for teachers in the learning process. Thirteen journals covering the topic were analyzed as part of a systematic literature review. The findings of this study highlight the importance of pedagogical skills in the teaching process to improve the quality of a teacher. When the teacher has chosen this pedagogical ability, the teacher will indirectly improve the quality of his teaching. Because within pedagogical abilities, teachers will also be asked to understand students' conditions so that the classroom atmosphere is more enjoyable. This research uses a systematic literature review method. The results of this research explain that pedagogical abilities have a huge influence in the world of education and we can say that pedagogical abilities are very important for a teacher to improve the quality of his teaching.